Sentence Completion Test – Research and Inspirational Tool for Industrial Designer - Dumitrescu, Andrei (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The traditional documentation techniques used by designers fail to capture the needs, expectations and interests of the subconscious of the targeted market segment. Sentence completion test is a technique that can identify these elements both at conscious level and subconscious level. The purpose of this research was to verify on a practical case the usefulness of the technique as a research and inspirational tool for designers and also to propose a test structure when applying the technique in the field of product aesthetics.